A Biomimetic Core–Shell Platform for Miniaturized 3D Cell and Tissue Engineering. (12th May 2015) - Agarwal, Pranay; Choi, Jung Kyu; Huang, Haishui; Zhao, Shuting; Dumbleton, Jenna; Li, Jianrong; He, Xiaoming
<x xml:space="preserve">Abstract</x> This article describes a biomimetic core–shell platform with a collagen‐based core and an alginate hydrogel shell for cell and tissue culture. With this system, chemical and physical properties of extracellular matrix (ECM) in the core microenvironment can be controlled to regulate proliferation and development of cells/tissues under miniaturized 3D culture.